XIII. studentská vědecká konference Katedry českého jazyka a literatury 18. března 2021 - Čermáková, Gabriela (Sborník prací Pedagogické fakulty Masarykovy univerzity, 2021)
Title in English: The XIIIth Student Academic Conference of the Department of Czech Language and Literature: 18th March 2021. Proceeding of the conference held on 18th March 2021. The publication contains studies by Gabriela Čermáková ("Contemporary Situation of Podkrkonošský Dialect"), Radim Ošmera ("The Methodology of the Research of Other Language"), Veronika Tinková ("Language Specifics in the Czech Language Education of Bilingual Children of Primary School Age in the Czech-French Environment"), Zuzana Procházková ("Alternative Methods in the Czech Language Education on Secondary Schools"), Miroslav Jindra ("I Am Vinnetou!?: Elements of Identifications with a Literary Work and Theatrical Performance of Children at 8-9 age"), Tereza Švandová ("What is Lettrism?"), Klára Březinová ("A Portrait of Virgin Mary in Elected Works of Jaroslav Durych"), Ondřej Zabloudil Pechník ("Jungle, My Love, or A Chesty Man and a Story Thief by Josef Formánek") and Alexandra Gončarenko ("A Motif of the Initiatory Journey in Works of Martin Ryšavý and Vladimír Sorokin").